Mengukur Tingkat Pemahaman Karyawan Terhadap Penanganan Limbah B3 Menggunakan Metode Deskriptif Di PT Fajar Budi Lestari: Measuring Employee Understanding of Hazardous Waste Management Using Descriptive Methods at PT Fajar Budi Lestari - Mohamad Arifin; Ratih Hastasari; Wawan Saputra (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study measures the level of understanding of PT. Fajar Budi Lestari employees regarding Hazardous and Toxic Waste (B3) handling procedures using a non-statistical quantitative descriptive method with a questionnaire survey. The sample for this research consists of all operational employees directly involved in B3 waste management. The results show that the majority of employees have a high level of understanding, especially in identifying important parts of SOPs (average score 4.48), differentiating between mandatory and additional procedures (average score 4.30), applying SOPs (average score 4.30), and reporting awareness (average score 4.48). However, some areas, such as understanding the location of Temporary Storage Sites (TPS), waste storage time limits, and emergency coordination procedures, still need improvement. Overall, employee understanding positively contributes to company compliance, although retraining, socialization, and routine simulations are still needed to maintain consistency.